2016
DOI: 10.1111/vde.12373
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cutaneous mycobiota in healthy and allergic cats using next generation sequencing

Abstract: The skin of healthy cats appears to have a more diverse fungal microbiota compared to previous studies, and a fungal dysbiosis is noted in the skin of allergic cats. Future studies assessing the temporal stability of the skin microbiota in cats will be useful in determining whether the microbiota sequenced using NGS are colonizers or transient microbes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 39 publications
4
68
0
4
Order By: Relevance
“…Meason-Smith et al found that dogs most clustered by individual, regardless of health condition [21]. This same clustering by individual, regardless of health, was also seen in a similar study done on cats [20]. In both studies, differences in relative taxa abundance between healthy and allergic animals were identified.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Meason-Smith et al found that dogs most clustered by individual, regardless of health condition [21]. This same clustering by individual, regardless of health, was also seen in a similar study done on cats [20]. In both studies, differences in relative taxa abundance between healthy and allergic animals were identified.…”
Section: Discussionsupporting
confidence: 52%
“…In both studies, differences in relative taxa abundance between healthy and allergic animals were identified. Overall, it seems that fungi on the skin of cats [20] and dogs [21] clusters mostly by individual animal, whereas bacteria seem to cluster mostly by body site [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, faecal antigen tests detect both field and vaccine strains of FPV and CPV. In one study evaluating three commercial CPV faecal antigen kits, 20% of cats vaccinated against FPV in the preceding 14 days returned positive test results [29].…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the canine mycobiota shifts in disease states, lowering fungal diversity and allowing certain fungal populations to predominate in skin lesions. Furthermore, the skin of atopic dogs also is described to be associated with altered skin barrier, such as caused by fillagrin mutations, whereas similar alterations in skin barriers have not been described or confirmed in allergic cats, which might explain why no alterations were seen in diversity in the feline allergic skin disease …”
Section: Dysbiosis Of the Skin Microbiome Is Associated With Skin Dismentioning
confidence: 99%